On optimization of projection methods for solving some classes of severely ill-posed problems. Issue 4 (2nd April 2016) - Solodky, S.G.; Myleiko, G.L.
Abstract : In the present paper, the issue of the optimal solving severely ill-posed problems is studied. The authors proposed projection scheme of discretization which is efficient with respect to the amount of used Galerkin information. By this scheme, the order-optimal estimates of quantities described information and algorithmic complexity are achieved.